Folklore as Local Culture-Based Material for Improving Students' Reading Comprehension of Narrative Text - Riryn Fatmawaty; Fita Faridah; Novi Rahmania Aquariza; Alfiyah Nurahmada (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The study aims to describe the use of folklore in the classroom to improve students’ reading comprehension and to ascertain the reactions of the students to this approach. 22 students in 9th Grade B at SMPN 1 Sugio are the subjects of the study, which employs the classroom action research methodology. Participation of the students to improve their reading comprehension is the theme of all the key phrases. The teacher needs to inspire the students more, though. Utilizing interviews, observations, and questionnaires, data is gathered. 14.28.% of students met the minimal mastery level criterion, according to their preliminary test results (KKM). The initial cycle was deemed ineffective. Students who attained the bare minimum mastery in The first cycle was deemed a failure. The percentage of students who met the minimal mastery level criterion (KKM) was only 53.57% or 15 students. The second cycle is regarded as a success. It was because 26 students, or 92.85% of the test participants, met the minimal mastery level criterion (KKM). The percentage of students who got up increased with each cycle, and the findings suggested that reading folklore could improve students' reading comprehension. Reading folklore in the classroom raises students' enthusiasm, enjoyment, and participation. Reading the narrative text through folklore can improve students' reading comprehension.